1392. Pharmacokinetic-Pharmacodynamic (PK-PD) Target Attainment Analyses to Support Inhaled ME1100 Dose Selection. (26th November 2018) - Bhavnani, Sujata M; Hammel, Jeffrey P; Lakota, Elizabeth A; VanScoy, Brian D; Nagira, Yu; Rubino, Christopher M; Sato, Nobuo; Koresawa, Tomokazu; Kondo, Kenichiro; Ambrose, Paul G
Abstract: Background: ME1100 (arbekacin inhalational solution) is an inhaled aminoglycoside being developed to treat patients with hospital-acquired and ventilator-associated bacterial pneumonia (HABP and VABP, respectively). PK-PD target attainment analyses were undertaken to evaluate ME1100 regimens for patients with HABP/VABP arising from Klebsiella pneumoniae (KP), Pseudomonas aeruginosa (PA) and Staphylococcus aureus (SA), including those with renal impairment. Methods: Data used included a population pharmacokinetic (PPK) model developed using Phase 1 and post-marketing PK data, nonclinical PK-PD targets from one compartment in vitro and/or in vivo infection models, and MIC data. Using parameter estimates from the PPK model (four-compartment model with first-order elimination), total-drug epithelial lining fluid concentration-time profiles were generated for simulated patients with varying creatinine clearance (CLcr; mL/minute/1.73 m 2 ) and by CLcr group. Twice daily (BID) ME1100 regimens ranging from 300 to 900 mg were assessed in simulated patients with CLcr >80 to ≤120 mL/minute/1.73 m 2 . Percent probabilities of PK-PD target attainment by MIC were determined based on total-drug ELF AUC:MIC ratio targets associated with 1- and 2-log10 CFU reductions from baseline for KP, PA and SA using Day 1 AUC. Regimens in simulated patients with renal impairment that best matched the BID regimen in the normal CLcr group with high percent probabilities of PK-PD target attainment and a low percent probability of C min > 2 mg/L were identified. Results: ME1100 600 mg BID in simulated patients with CLcr >80 to ≤120 mL/minute/1.73 m 2, with 600 mg once daily, 450 mg BID and 600 mg BID in simulated patients with CLcr of 0 to ≤30, >30 to ≤50 and >50 to ≤80 mL/minute/1.73 m 2, respectively, achieved high percent probabilities of PK-PD target attainment based on PK-PD targets for a 1-log10 CFU reduction from baseline at relevant MIC values for KP, PA and SA, and relatively lower C min values. In simulated patients with varying CLcr who received these regimens, high percent probabilities of PK-PD target attainment were achieved for KP, PA and SA at the upper margins of the MIC distributions (Figures 1–3). Conclusion: The data provide support for ME1100 dose selection for patients with HABP/VAPB. Disclosures: S. M. Bhavnani, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. J. P. Hammel, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. E. A. Lakota, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. B. D. VanScoy, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. Y. Nagira, Meiji Seika Pharma Co. Ltd.: Employee, Salary. C. M. Rubino, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support. N. Sato, Meiji Seika Pharma Co. Ltd.: Employee, Salary. T. Koresawa, Meiji Seika Pharma Co. Ltd.: Employee, Salary. K. Kondo, Meiji Seika Pharma Co. Ltd.: Employee, Salary. P. G. Ambrose, Meiji Seika Pharma Co. Ltd.: Research Contractor, Research support.